Penggunaan Wordwall Untuk Meningkatkan Motivasi Belajar Pada Mata Pelajaran IPA di Sekolah Dasar: Literature Review - Syahyadi, Deni; Dwi Fajariyanto, Septian; Rifqy Ash-Shiddiqy, Ahmad (LPPM Universitas Terbuka, 2024)
This article discusses the use of the technology-based learning platform Wordwall in the context of the Natural Science (IPA) subject at the elementary school level. Natural Science plays a crucial role in shaping students' understanding of natural phenomena and scientific processes, but student motivation in this subject is often a challenge. Wordwall has proven effective in increasing student participation, building conceptual understanding, and enhancing learning motivation. This literature review article analyzes several studies related to the use of Wordwall in the context of IPA in elementary schools, highlighting the positive impact of Wordwall on student learning motivation. The research employs a literature review method and evaluates three articles that focus on the use of Wordwall in IPA education in elementary schools. The results of the research indicate that the use of Wordwall effectively enhances student learning motivation, especially during the COVID-19 pandemic. This medium helps boost students' interest in learning and enables an engaging learning experience. In conclusion, the utilization of Wordwall in elementary education has the potential to improve student learning motivation, and educational innovations should be considered to ensure sustainable learning quality.